Megalith of the Wharton's Duct: Review of Literature and a Case Report - Sercan Küçükkurt (Acta Odontologica Turcica)
Sialolithiasis, the most common disorder affecting salivary glands, occurs when calcified formations obstruct the ducts or glands. Typically, these formations, known as sialoliths, measure between 5 and 10 mm; however, those exceeding 15 mm are classified as megaliths. While sialoliths commonly manifest in the submandibular glands, they can develop in any salivary gland duct, with the Wharton’s duct of the submandibular gland being a frequent site. These stones, formed from calcified organic material within the secretory system, can lead to pain, swelling, and disruptions in saliva flow. Chronic sialolithiasis, the primary contributor to acute and chronic infections in salivary glands, is closely associated with stone formation. The precise cause remains unclear, yet it is linked to chronic sialadenitis and partial obstruction. On the contrary, megaliths are exceptionally rare and tend to occur more frequently in male patients. The present article presents a case involving a 19 mm long megalith detected at the duct mouth of the left submandibular gland, which was treated through surgical intervention. Additionally, a comprehensive literature review on this specific topic was conducted.